Management of severe atopic dermatitis in adult patients - Kobusiewicz, Aleksandra; Zalewska-Janowska, Anna M.; Lesiak, Aleksandra; Narbutt, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2020)
Atopic dermatitis is a chronic recurrent inflammatory condition of the skin. It can coexist with other atopy-related disorders, e.g. bronchial asthma, allergic rhinitis or food allergy. Beacuse of its chronic course and concomitance of pruritus, atopic dermatitis considerably decreases the quality of life of patients and their family members. Management of atopic dermatitis mainly involves appropriate skin care and daily application of emollients, combined with topical anti-inflammatory treatment. It is essential to initiate systemic immunosuppressive therapy in moderate or severe atopic dermatitis. The aim of the study is to present current therapeutic options for atopic dermatitis in adults, with particular consideration given to the approved biological treatment. Dupilumab was included in the management algorithm as the first-line treatment in moderate or severe atopic dermatitis, unresponsive to topical therapy and in cases in which systemic treatment is contraindicated.